PENGUATAN PENDIDIKAN KARAKTER BERBASIS INDOOR AND OUTDOOR MELALUI PEMBELAJARAN TEMATIK DI SEKOLAH DASAR NEGERI KECAMATAN SUNGAI PINYUH - Wardah, Wardah; Sulistyarini, Marzuki; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed at describing the integration of values in strengthening indoor and outdoor based character education, focused on its planning, implementation, evaluation, and barriers through thematic learning at Sei Pinyuh Public Primary School. This is a descriptive qualitative research, conducted in Public Primary School (SD Negeri) 02 Sungai Pinyuh. The data collection techniques used were observation, interview, and documentation study. The main instrument was the researcher herself, supported by the use of observation sheet, interview guide, and document analysis. The results showed that strengthening indoor and outdoor based character education through thematic learning at Sei Pinyuh Public Primary School revealed: planning, implementation, evaluation, and obstacles faced by teachers in integrating character values. The lesson planning used was not made by the teachers themselves; however, it had already shown in the integration of character education. In terms of implementation, the teachers did it through learning activities, learning methods, spontaneous activities, disciplinary reinforcement, and conducive atmosphere development. Learning evaluation was done well through authentic assessment, including assessment of the process and assessment of learning outcomes. The obstacles faced by the teachers were limited facilities and infrastructure in the form of learning media, learning methods, attitude assessment, and family supports.Keywords: Strengthening Character Education, Thematic Learning, primary school